PCI Connector Tilt Detection via Fringe Projection - Vithyacharan, Retnasamy; M. M., Ratnam (Universiti Malaysia Perlis (UniMAP), 2010)
The evolution of printed circuit board assembly (PCBA) in complexity and miniaturization components coupled with total quality trends are causing the replacement of human inspectors with the automated visual inspection (AVI) systems. Human inspectors can only detect 50% of visible PCBA board defects and the repetitive and demanding nature of inspection makes concentration di cult to maintain for human inspectors. Human inspectors are prone to visual fatigue and make subjective decisions on defects. AVI systems, however, have high consistency, repeatability and operate round-theclock. An AVI system with a single overhead camera has exibility limitations for inspecting certain types of defects, such as tilted or lifted pin-through-hole (PTH) components.